Knowledge and preparedness of healthcare providers towards bioterrorism - Abdullah Nofal; Isamme AlFayyad; Nawfal AlJerian; Jalal Alowais; Meshal AlMarshady; Anas Khan; Humariya Heena; Ayah Sulaiman AlSarheed; Amani Abu-Shaheen (BMC, 2021)
Abstract Background Several emergent circumstances require healthcare providers to recognize the unusual and dangerous and pathogenic agents. An in-depth literature review showed that studies about bioterrorism preparedness amongst healthcare providers are lacking. Therefore, this study aimed to investigate the knowledge and preparedness level of first emergency respondents towards bioterrorism events. Methods This study has a cross-sectional design and was carried out at the Emergency departments and poison control centers/clinical laboratories three in major tertiary care hospitals in Riyadh, Saudi Arabia. The subjects were randomly selected to complete the self-administered questionnaire to collect study outcomes. Results A total of 1030 participants were included in the final data analysis. The mean knowledge score in the basic concepts of bioterrorism and introductory clinical presentations of bioterrorism-related agents was 4.92 ± 1.86 out of 12 points. Moreover, the findings showed a mean knowledge score of 22.80 ± 3.92 out of 38 in the bioterrorism preparedness and governing policies and procedures. Respondents who received previous training in bioterrorism preparedness had a significantly higher number of perceived benefits than those not sure and without prior training (z = − 2.67, p = 0.008) and (z = − 4.4, p < 0.0001), respectively. About 79.4% of participants did not have previous training in bioterrorism preparedness, but 68.7% expressed willingness in the institution's response and control to assist in a bioterrorist attack incident. Conclusion Although healthcare professionals have reported their desire to help in bioterrorism events, they need to enhance their knowledge of bioterrorism preparedness.